4‐Substituted thieno[2, 3‐d]pyrimidines as potent antibacterial agents: Rational design, microwave‐assisted synthesis, biological evaluation and molecular docking studies. (22nd June 2017) - Gill, Rupinder K.; Singh, Harpreet; Raj, Tilak; Sharma, Anuradha; Singh, Gagandeep; Bariwal, Jitender
Abstract : In an attempt to discover a new class of antibacterial agents with improved efficacy and to overcome the drug‐resistant problems, some novel 4‐substituted thieno[2, 3‐ d ]pyrimidines have been synthesized via microwave‐assisted methodology and evaluated for their in vitro antibacterial activity against various pathogenic bacterial strains. Compounds12 b and13 c showed the promising inhibitory potencies against Staphylococcus aureus, Bacillus subtilis, Pseudomonas aeruginosa and Escherichia coli with MICs ranging from 2 to 10 μg/ml. Compound13 c was also found to be highly potent against methicillin‐resistant S. aureus (MRSA) with MIC value of 4 μg/ml. Docking simulation studies have been performed to unravel the mode of action and association study indicate the binding of potent compounds with DHPS enzyme. In silico ADME studies suggest the drug‐like characteristics of the potent compounds. Abstract : 4‐Substituted thieno[2, 3‐ d ]pyrimidines were designed, synthesized and evaluated for antibacterial activity. Docking studies suggest the bacterial dihydropteroate synthase inhibitory activity of potent compounds. Hence, its binding affinity with DHPS enzyme was also determined.